Pathological changes in lungs of horses affected with equine infectious anemia - Santos, Jefferson Andrade dos; Peres, Amaury Romeiro (Pesquisa Agropecuaria Brasileira, 2014)
The histopathological changes in lungs of horses affected with Equine Infectious Anemia, were studied. The frequency of such lesions was high (it was found in 11 cases out of 12 studied.) Hemosiderosis was the most marked lesion. In extensive lesions, the hemosidorin was found apparently free in large masses in the connective tissue of the broncho-vascular axis (6 cases). In mild changes, it was observed in macrophages vases in the capillary lumina and sometimes in the alveolar lumen (5 cases). In some cases, there was sclerosis of the connective tissues of the broncho-vascular axis, interlobular septa and interstitial tissue. There were also alveolar emphysemata. The authors stress that such lesions could be of value for diagnosis of this disease.